Evaluation of Entrance Surface Dose in Chest Radiography Using Clinical Images: Estimation of Subject Thickness Using Two-direction Radiography - Asada, Yasuki; Ono, Koji; Ichikawa, Takuma (Japanese Journal of Radiological Technology, 2018)
The International Commission on Radiological Protection recommends adaptation of the diagnostic reference levels as an indicator of optimization of protection, and diagnostic reference levels of 2015 were also published in Japan in 2015 (Japan DRLs 2015). The entrance surface dose (ESD) is evaluated to the published standard subject thickness in Japan DRLs 2015. However, the standard radiographic settings of each facility may not be a radiographic condition of the standard subject thickness of Japan DRLs 2015. We measure and record the thickness of the subject in every examination, and it can solve this problem, but it is difficult to carry out it in the actual clinical scene. In this study, we aimed to estimate the subject thickness by using chest clinical images and to calculate ESD for each radiography. We evaluated and compared with Japan DRLs 2015 using these data. The subject thickness was estimated from 200 cases of digital imaging and communications in medicine (DICOM) image obtained by both the frontal and lateral views of the chest radiography. Also, at the same time, the radiographic settings were acquired from the information of the DICOM tag. The subject thickness was 23.60 cm on the average, and the median of the ESD was 0.104 mGy. Also, the median of the ESD at the standard subject thickness of 20 cm in Japan DRLs 2015 was 0.075 mGy. The ESD can be calculated without measuring the body thickness of the patient of every examination by using the method of this study.